Jim Gaffigan stand-up spotlight [videorecording (DVD)] - Gaffigan, Jim (Mill Creek Entertainment, 2023)
Grammy-nominated comedian Jim Gaffigan shares his observations on museums, dog birthdays, medical issues, lying to children, and more in two hilarious hour-long stand-up specials you'll be watching again and again!